Management of Cultural Diversity and Employee retention - Goda Baddage, Isuru (My University, 2025)
ABSTRACT: This study has investigated how to manage cultural diversity and how it affects employee retention in a culturally varied workforce in Finland. Organizational cultural diversity has become more widely acknowledged as a challenge as well as an opportunity that affects communication and employee experiences. To investigate how cultural diversity is managed and how it impacts employee retention in a multicultural workplace is the purpose of this study. To gather information from supervisors and workers, it has used semi-structured interviews and focus groups. Purposive sampling was used to choose employees to derive data from various cultural backgrounds. Abductive analysis has been applied to systematically integrate theory and data. The results of the study express how cultural diversity has affected employees' sense of belonging and organizational commitment. Employees expressed feelings of exclusion due to unfairness in job distribution, breaks, and disciplinary actions. This lowered morale and raised the chance of turnover. The study emphasizes that even while the business complies with collective bargaining agreements, there are still obstacles to creating an accepting and equal workplace for workers from all cultural backgrounds. When it is not actively controlled, it creates perceived differences and barriers to communication. Workplace links, perceived sacrifices, and organizational fit have all significantly impacted employees' embeddedness and subsequently their desire to remain with the company. It has been discovered that effective diversity management techniques, such as fair treatment and inclusive communication tactics, improve employee retention. Findings shows that managing cultural diversity increases workers' psychological ties to the company and it improve retention . Organizations are encouraged to create organized diversity management procedures and improve leadership abilities in overseeing cultural groups. Further research is recommended to examine long-term shifts in employee retention in workplaces that are becoming more diverse. KEYWORDS cultural diversity, employee retention, job embeddedness, social identity theory, diversity management
Keywords: multiculturalism; employees; work communities; workplaces; workplace culture; culture; cultural differences; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business